1986
DOI: 10.1016/0014-5793(86)80088-6
|View full text |Cite
|
Sign up to set email alerts
|

Alanine and lactate as gluconeogenic substrates during late gestation

Abstract: Rates of alanine incorporation into glucose by isolated liver cells of fed rats are 5-fold higher than those observed when lactate was used as substrate. The rates of g~~eoneogenesis from alanine and lactate in isolated liver cells of fed pregnant rats increase 50 and ~~%, respectively, over virgins during the last 3 days of gestation. The results support the existence of an increase in the aianine-glucose cycle in the iate pregnancy as an important homeostatic pathway in the supply of glucose to the growing f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

1987
1987
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…Regarding individual amino acids, alanine and glycine accounted for a major proportion of amino acids taken up by the liver, especially in fed pregnant rats. This finding is in accordance with the higher rates of conversion of alanine into glucose found in hepatocytes isolated from fed late-pregnant rats compared with those from fed virgin controls (Cuezva et al, 1986).…”
Section: Substrate Availabilitysupporting
confidence: 89%
“…Regarding individual amino acids, alanine and glycine accounted for a major proportion of amino acids taken up by the liver, especially in fed pregnant rats. This finding is in accordance with the higher rates of conversion of alanine into glucose found in hepatocytes isolated from fed late-pregnant rats compared with those from fed virgin controls (Cuezva et al, 1986).…”
Section: Substrate Availabilitysupporting
confidence: 89%
“…In contrast, with the progressive insulin-insensitivity that the peripheral organs develop toward the end of pregnancy, the hepatic glucose production remains sensitive to the stimulation of this hormone throughout gestation (Butte, 2000). Gluconeogenesis is limited during gestation, probably to maintain high levels of AA (Butte, 2000;Kalhan et al, 1997), whereas it occurs in some extent at the end of pregnancy as an important homeostatic pathway in the supply of glucose to the growing fetus (Cuezva et al, 1986). Besides the regulation of energy homeostasis, the liver plays another essential role during pregnancy by participating in the elimination of waste molecules accumulated by the embryo metabolism (McArthur et al, 2003;van Herwaarden et al, 2007).…”
Section: Consequences Of Placentation For Female Hepatic Metabolismmentioning
confidence: 95%
“…It has been reported that the human embryo can catabolize amino acids to produce energy [ 33 ]. It is also possible that the catabolic metabolism of amino acids is enhanced, as studies on pregnant rats have shown that tryptophan catabolism is increased in late pregnancy compared with mid-pregnancy [ 34 ]. Unexpectedly, amino acid concentrations in amniotic fluid were positively correlated with maternal lipid intake; conversely, they were negatively correlated with carbohydrate intake.…”
Section: Discussionmentioning
confidence: 99%